Fluoroquinolones and Aortic Diseases: Is There a Connection - Carino, Davide (Aorta (Stamford), 2019)
Fluoroquinolones (FQs) are one of the most commonly prescribed classes of antibiotics. Their high tissue distribution and broad-spectrum antibacterial coverage make their use very attractive in numerous infectious diseases. Although generally well tolerated, FQs have been associated with different adverse effects including dysglycemia and arrhythmias. FQs have been also associated with a series of adverse effects related to collagen degradation, such as Achilles tendon rupture and retinal detachment. Recently, an association between consumption of FQs and increased risk of aortic aneurysm and dissection has been proposed. This article reviews the pathogenesis of thoracic aortic diseases, the molecular mechanism of FQ-associated collagen toxicity, and the possible contribution of FQs to aortic diseases.